2015
DOI: 10.1093/tropej/fmv058
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric HIV–HBV Coinfection in Lusaka, Zambia: Prevalence and Short-Term Treatment Outcomes: Table 1.

Abstract: Hepatitis B virus (HBV) is endemic in Africa, where it may occur as an HIV coinfection. Data remain limited on HIV-HBV epidemiology in Africa, particularly in children. Using programmatic data from pediatric HIV clinics in Lusaka, Zambia during 2011-2014, we analyzed the prevalence of chronic HBV coinfection (defined as a single positive hepatitis B surface antigen [HBsAg] test) and its impact on immune recovery and liver enzyme elevation (LEE) during the first year of antiretroviral therapy. Among 411 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…This was in accordance with the prevalence of 1.2% which was reported by Telatela et al in 2007 in Tanzania and a prevalence of 2.0% reported by Abera et al in 2014 in Ethiopia [5,8]. However, the prevalence in these 3 studies was significantly lower than the respective seroprevalences in Nigeria, Ivory Coast, Zambia, India and China [9][10][11][12][13] (Table 3). Muro et al at KCMC found a prevalence of 7.0% among HIV infected children [6].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was in accordance with the prevalence of 1.2% which was reported by Telatela et al in 2007 in Tanzania and a prevalence of 2.0% reported by Abera et al in 2014 in Ethiopia [5,8]. However, the prevalence in these 3 studies was significantly lower than the respective seroprevalences in Nigeria, Ivory Coast, Zambia, India and China [9][10][11][12][13] (Table 3). Muro et al at KCMC found a prevalence of 7.0% among HIV infected children [6].…”
Section: Discussionsupporting
confidence: 89%
“…Other studies reported also low CD4 counts in HBV/HIV co-infected individuals [16][17][18]. The study conducted in Nigeria reported lower CD4 count among HBV-HIV co-infected children compared to those who had HIV infection only [18], as was found by Peebles et al in Zambia [11].…”
Section: Discussionmentioning
confidence: 62%
“…Prevalence was lower (~2%) among samples in India, Malawi, Poland, Spain and the United States, among HIV‐positive paediatric patients. Prevalence was higher in Benin (9.6%), Rwanda (6.8%), Tanzania (7%) and Zambia (10.4%) among children <16 years recruited through HIV clinics . HIV‐exposure categories were not consistently reported.…”
Section: Resultsmentioning
confidence: 94%
“…A high prevalence (32.6%) was also found in Thailand among young people perinatally infected with HIV (mean age 14 years). 49 48,[55][56][57] HIV-exposure categories were not consistently reported.…”
Section: Children and Young Peoplementioning
confidence: 99%
“…While the profile of disease in HIV-co-infected patients in Africa has been the subject of considerable interest, 14 16 including children, 17 paradoxically, fewer studies have been published about Africans with monoinfection. There are data to suggest that HBV acquisition in Zambia occurs horizontally in early childhood, rather than vertically, 18 in common with other data from southern Africa.…”
Section: Discussionmentioning
confidence: 99%